2017
DOI: 10.1038/ni.3711
|View full text |Cite
|
Sign up to set email alerts
|

IRAP+ endosomes restrict TLR9 activation and signaling

Abstract: Retention of intracellular Toll-Like Receptors (TLRs) in the endoplasmic reticulum prevents their activation under basal conditions. TLR9 is activated by sensing ligands in specific endosomal/lysosomal compartments. Here, we describe the identification of insulin responsive aminopeptidase (IRAP) endosomes as major cellular compartments for the early steps of TLR9 activation in dendritic cells (DCs). Both TLR9 and its ligand CpG were found as cargo in IRAP endosomes. In the absence of IRAP, CpG and TLR9 traffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 47 publications
4
49
0
Order By: Relevance
“…Cathepsin/AEP protease activity assays were performed as previously described 66 using 1 µg of protein in lysis buffer (50 mM Tris/150 mM NaCl/1% NP40) on a Mithras LB 940 microplate reader by measuring the release of fluorescent N-Acetyl-Methyl-Coumarin substrate (100 µM) in citrate buffer (pH 5.5) at 37 °C, detected using 380/440 nm excitation/emission. Leucyl aminopeptidase activity was measured as previously described 67 in 50 mM Tris buffer, pH 7.5/1 mM DTT and 100 µM substrate except that activity was measured on 3 µg of whole-cell or purified phagosome lysates without anti-IRAP immunoprecipitation. Specific substrates for AEP (Z-Ala-Ala-Asn- NHMec), CatB/L (Z-Phe-Arg-NHMec), CatS (Z-Val-Val-Arg-NHMec) and IRAP substrate (Leu-AMC) were purchased from Bachem.…”
Section: Methodsmentioning
confidence: 99%
“…Cathepsin/AEP protease activity assays were performed as previously described 66 using 1 µg of protein in lysis buffer (50 mM Tris/150 mM NaCl/1% NP40) on a Mithras LB 940 microplate reader by measuring the release of fluorescent N-Acetyl-Methyl-Coumarin substrate (100 µM) in citrate buffer (pH 5.5) at 37 °C, detected using 380/440 nm excitation/emission. Leucyl aminopeptidase activity was measured as previously described 67 in 50 mM Tris buffer, pH 7.5/1 mM DTT and 100 µM substrate except that activity was measured on 3 µg of whole-cell or purified phagosome lysates without anti-IRAP immunoprecipitation. Specific substrates for AEP (Z-Ala-Ala-Asn- NHMec), CatB/L (Z-Phe-Arg-NHMec), CatS (Z-Val-Val-Arg-NHMec) and IRAP substrate (Leu-AMC) were purchased from Bachem.…”
Section: Methodsmentioning
confidence: 99%
“…The N-terminus of IRAP is also believed to be important for tethering specialized endosomes to the cytoskeleton via binding of interacting proteins including tankyrase ( Chi and Lodish, 2000 ), acyl-coenzyme A dehydrogenase ( Katagiri et al, 2002 ), formin homology domain (FHOD) ( Babdor et al, 2017 ), p115 ( Hosaka et al, 2005 ), Vps35 ( Pan et al, 2019 ), and Akt substrate of 160 kDa (AS160) ( Figure 2 ; Peck et al, 2006 ). This has been clearly demonstrated in dendritic cells, in which the role of the N-terminal domain of IRAP has only recently been implicated in immune function.…”
Section: Recognising the N-terminal Domain Of Irapmentioning
confidence: 99%
“…This has been clearly demonstrated in dendritic cells, in which the role of the N-terminal domain of IRAP has only recently been implicated in immune function. A comprehensive study by Babdor et al (2017) revealed that anchorage of endosomes containing toll-like receptor 9 (TLR9) to the actin cytoskeleton by the N-terminus of IRAP via the interacting protein, FHOD4, prevents TLR9 activation. Thus, in the absence of IRAP, the trafficking of TLR9 to lysosomes and subsequent activation was enhanced in cultured dendritic cells and in mice following bacterial infection, leading to an increased secretion of pro-inflammatory cytokines ( Babdor et al, 2017 ).…”
Section: Recognising the N-terminal Domain Of Irapmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that P-LAP/IRAP plays important roles in the modulation of several brain functions. This enzyme is also an important player in host defense systems, such as antigen cross-presentation, and Toll-like receptor 9 signaling (Saveanu et al, 2009;Babdor et al, 2017). P-LAP/IRAP trims antigenic peptides presented by MHC class I molecules, and also modulates Toll-like receptor 9 trafficking to lysosomes via interaction with FHOD4 (Saveanu et al, 2009;Babdor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%